Parenting Stress and Physical Abuse against Children with Disabilities - Rizqi Nur Aini; Tantut Susanto; Hanny Rasni (INKLUSI, 2020)
Children with disabilities often experience physical violence committed by caregivers. This study aims to identify the relationship between stress in caring for physical violence committed against children with disabilities. The study used a cross-sectional design to examine 76 parents with children with disabilities selected by convenience sampling techniques. Of the 76 participants, 35 (46.1%) parents physically abused children with disabilities. The most common type of violence is hitting (74.3%). Parenting stress may be felt by parents because there is a relationship between caregiving stress with physical violence (Z= -2.85; p-value= 0.004). Lack of access to information related to adaptive care makes parents in Indonesia still consider physical violence, such as hitting children, is a natural thing. The research concludes that there is a relationship between parental stress and physical violence against children with disabilities. Health workers are expected to be able to teach parents how to improve coping mechanisms to reduce parenting stress so that parenting behavior becomes adaptive.[Anak difabel sering mengalami kekerasan fisik yang dilakukan oleh pengasuh. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara stres dalam pengasuhan dengan kekerasan fisik yang dilakukan terhadap anakdifabel. Penelitian menggunakan desain cross-sectional untuk meneliti 76 orang tua dengan anak difabel yang dipilih dengan teknik convenience sampling. Dari 76 partisipan, 35 (46,1%) orang tua melakukan kekerasan fisik terhadap anak difabel. Jenis kekerasan yang paling banyak dilakukan adalah memukul (74,3%). Stres pengasuhan mungkin dirasakan oleh orang tua karena terdapat hubungan antara stres pengasuhan dengan kekerasan fisik (Z=-2,85; p-value = 0.004). Kurangnya akses informasi terkait pengasuhan yang adaptif menyebabkan orang tua di Indonesia masih menganggap kekerasan fisik seperti memukul anak merupakan hal yang wajar. Penelitian menyimpulkan bahwa terdapat hubungan antara stres pengasuhan dengan kekerasan fisik terhadap anak difabel. Tenaga kesehatan diharapkan dapat mengajarkan orang tua dalam meningkatkan mekanisme koping untuk menurunkan stres pengasuhan sehingga perilaku pengasuhan menjadi adaptif.]